AN ANALYSIS OF THE REPEATED CLAIMS OF THE END OF PRIVACY - John, Nicholas; Peters, Benjamin (AoIR Selected Papers of Internet Research, 2014)
This paper enquires into the nature of talk about the end of privacy. The motivation for this follows from the observation that privacy has been repeatedly declared dead by various observers almost from the day it was declared alive. How is this repetitiveness sustained? Are privacy eulogists aware that similar eulogies have already been delivered, many times over? How might we suppose that readers respond to these repeated declarations of the end of privacy? While various causes are posited for the death of privacy, the place of the internet and communications technologies is clearly central in the narrative of what we call ‘privacy endism’. The evidentiary basis for this paper is a corpus of 101 newspaper articles that claim that privacy has ended, or warn about its imminent demise, and that were published between November 1990 and May 2012. These articles were subjected to qualitative analysis.